CEREBRAL AUTOREGULATION IN HEAD INJURY - Apsari Dewi, Ni Made Ayu (E-Jurnal Medika Udayana; vol 2 no 9 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE A characteristic feature of the cerebral circulation is that the cerebral blood flow is dynamically adjusted to protect brain blood from changes in perfusion pressure. Cerebral blood flow tends to remain constant over a range of systemic blood pressures (cerebral auto regulation). Increases and decreases of the arterial CO 2 tension (P a CO 2 ) will increase and decrease cerebral blood flow by cerebral vasodilatation and vasoconstriction, independent of cerebral auto regulation (CO 2 reactivity of the brain). After brain injury, cerebral flow auto regulation gets impaired in most patients. In patient with severe traumatic brain injury, impaired CO 2 reactivity occurred in early stage trauma. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: auto regulation; CO2 reactivity; head injury; pat physiology